Optimisation of silicon adhesive cure using differential scanning calorimetry analysis - Lee, Chow Sim. (2008)
Polymer curing is an essential part of electronic manufacturing process. Most electronic components are sensitive to prolong heat exposure and has negative performance impact. Often, non-value-added time is wasted in post-cooling the part to acceptable temperature before the next process. Thus, the ability to reduce curing cycle time and limit the component to high heat exposure will not only improve daily throughput but also enhance product performance. In this project, the author employed the technique of combining various maximum rate of heat evolution at selected cure temperature using Differential Scanning Calorimetry (DSC) thermal analysis to improve cure efficiency. The maximum cure temperature was reduced from 150°C to 140°C and the total cure time reduced from 48 minutes to 27 minutes. This report focuses on thermal analysis methods for chemical or phase changes, in particular by the use of the DSC analysis. To obtain an accurate and reproducible DSC thermograph, the author also provided a rudimentary documentation of all critical factors affecting the DSC study. Interpretation of DSC curves and factors affecting DSC results such as selection of sample size, sample preparation, calibration, experiment setup, heating rate and instrument characteristics were also discussed in detail in this report.